Hypotensive effect of aqueous and methanolic extracts from syzygium polyanthum (wight) walp leaves on the evaluation of nitric oxide pathway - an in vivo approach - Zulazmi, Nurul Atiqah (Universiti Sains Malaysia, 2013)
Syzygium polyanlhum (Serai kayu) is one of the traditional herbs (ulam) that eaten freshly by Malaysian and traditionally used as a medicine for hypertension, stroke, diabetes, hypercholesterolemia, cataracts, rashes, itchy and sore stomach. Previous studies have established the biological profile and phytochemical analysis of S. polyanthum that contain anti-hypertensive associated compounds. Even though this plant has known to have potential in the treatment of hypertension but the pharmacological mechanism of it is still unclear. In this research, we want to determine the cardiovascular effects of S. polyanthum extracts on blood pressure of anaesthetised rat and the involvement of nitric oxide system in the hypotensive effect. S', polyanthum aqueous extract (AESP) was prepared by freezed-dried. The residue obtained was extract in Soxhlet extractor and successively fractionated using methanol to obtain the methanol extract (Meth-AESP). Both of the extracts were studied by administered through the left jugular vein of anaesthetised rat and the blood pressure is recorded through the cannulated right common carotid artery. Both Meth-AESP and AESP (100 mg/kg) significantly reduced the rat’s mean blood pressure (MBP) (p<0.001). With the addition of L-NAME (20 mg/kg), the hypotensive response of Meth-AESP was significantly reduced (p<0.001). However, L-NAME did not affect the hypotensive response of AESP (p>0.05). We concluded that that hypotensive mechanism of Meth- AESP is likely mediated through the involvement of nitric oxide system.